B21 Ribosomal transcription is regulated by PGC-1alpha and disturbed in huntington's disease. (13th September 2016) - Weydt, Patrick; Jesse, Sarah; Bayer, Hanna; Alpei, Marius; Zügel, Martina; Mulaw, Medhanie; Malmsheimer, Silke; Singh, Karmveer; Steinacker, Jürgen; Schumann, Uwe; Ludolph, Albert; Scharffetter-Kochanek, Karin; et al.
Abstract : Background/aims: PGC-1α is a versatile inducer of mitochondrial biogenesis and responsive to the changing energy demands of the cell. As mitochondrial ATP production requires proteins that derive from translation products of cytosolic ribosomes, we asked whether PGC-1α directly takes part in ribosomal biogenesis. Methods/techniques: In a first step, we performed in vitro assays using confocal microscopy and Chromatin-immunoprecipitation in HEK and N2A cells. The results were confirmed in co-immunoprecipitation assays. Secondly, different tissues of WT and PGC-1α KO mice were investigated. To translate the in vitro data into in vivo, we cultivated primary cells of brown adipose tissue of WT and PGC-1α KO mice to reproduce the in vitro results. For translation into the human system, we investigated muscle biopsies of 21 healthy humans as well as 6 patients with Huntington's disease. Results/outcome: We show that a fraction of cellular PGC-1α localises to the nucleolus, the site of ribosomal biogenesis. Upon activation it strongly binds the ribosomal DNA and boosts recruitment of RNA polymerase I and UBF to the rDNA promoter. This induces RNA polymerase I transcription under different stress conditions in cell culture and mouse models as well as in healthy humans and is impaired already in early stages of human Huntington's disease. Conclusions: These results extend the hypothesis, that PGC-1α regulates rDNA transcription under different stress conditions to the observation that even basal levels of ribosomal biogenesis are affected by dysregulation of PGC-1α in Huntington's disease. This novel molecular link between ribosomal and mitochondrial biogenesis helps to explain sarcopenia and cachexia in diseases of neurodegenerative origin.